Hasil Konsepsi Ibu Hamil yang Terkonfirmasi Positif COVID-19 - Izati Maftuha; Arief Bakhtiar; Dewi Setyowati (Universitas Batanghari Jambi, 2023)
POGI noted that were 536 pregnant women who were confirmed positive COVID-19 in the past year and 3% of them died. COVID-19 infection in affected pregnant women can affect the mother's conception results. This study aims to describe the results of conception in pregnant women who are confirmed positive for COVID-19. This research is a descriptive observational study with a retrospective approach. The research subjects involved in this study were 31 pregnant women who were positive for COVID-19 and gave birth at Dr. Soetomo Surabaya during January - December 2021. The sampling technique used purposive sampling. Patient data was taken from medical record data. 19 people (61%) tested positive for COVID-19 without symptoms and 12 people with symptoms (39%). 18 people (58%) gave birth by vaginal delivery, 12 people (39%) SC, and 1 people (3%) forceps extraction. There are 3 (10%) mothers who died. Conception results of normal healthy babies were 22 babies (71%), low birth weight 6 babies (4%), IUGR 2 babies (7%), IUFD 1 baby (4%), premature birth 11 people (35%), infant death 2 people (6%), and one baby (3%) who tested positive for COVID-19. Â Most of the results of the conception of pregnant women with confirmed COVID-19 are normal healthy babies.